Endothelial cells modulate renin secretion from isolated mouse juxtaglomerular cells. - Kurtz, A (1991)
Utilizing cocultures of mouse renal juxtaglomerular cells with bovine microvascular endothelial cells, we have examined whether endothelial cells exert direct influence on renin secretion from renal juxtaglomerular cells. In the presence of endothelial cells both spontaneous and forskolin (10 microM) or isoproterenol (10 microM) stimulated renin release were markedly attenuated. The stimulatory effect of the calmodulin antagonist calmidazolium (10 microM) on renin secretion was not altered by endothelial cells, whereas the stimulatory effect of ethylisopropylamiloride (50 microM) an inhibitor of sodium-proton exchange was enhanced in the presence of endothelial cells. Indomethacin (10 microM) and NG-monomethyl-l-arginine (NMMA) (1 mM) used to inhibit cyclooxygenase activity and production of endothelium-derived relaxing factor (EDRF) decreased spontaneous renin release in the presence of endothelial cells only, but had no effect on forskolin stimulated renin secretion. Endothelin (1 microM) inhibited cAMP stimulated renin release both in the absence and in the presence of endothelial cells. ATP (10 microM) which acts on both endothelial and juxtaglomerular cells via purinergic P2 receptors inhibited cAMP stimulated renin release only in the absence but not in the presence of endothelial cells. This modulatory effect of endothelial cells was no altered by indomethacin nor by NMMA. Taken together, our findings provide first evidence for a local control function of the endothelium on cAMP stimulated renin secretion from renal juxtaglomerular cells, which could in part be mediated by endothelin.